Duration of exclusive breastfeeding is a positive predictor of iron status in 6‐ to 10‐month‐old infants in rural Kenya. Issue 4 (29th November 2016) - Uyoga, Mary A.; Karanja, Simon; Paganini, Daniela; Cercamondi, Colin I.; Zimmermann, Sophie A.; Ngugi, Benjamin; Holding, Penny; Moretti, Diego; Zimmermann, Michael B.
Abstract: The prevalence of iron‐deficiency anemia (IDA) is high in infants in Sub‐Saharan Africa. Exclusive breastfeeding of infants to 6 months of age is recommended by the World Health Organization, but breast milk is low in iron. Some studies suggest exclusive breastfeeding, although beneficial for the infant, may increase risk for IDA in resource‐limited settings. The objective of this study was to determine if duration of exclusive breastfeeding is associated with anemia and iron deficiency in rural Kenyan infants. This was a cross‐sectional study of 6–10‐month‐old infants (n = 134) in southern coastal Kenya. Anthropometrics, hemoglobin (Hb), plasma ferritin (PF), soluble transferrin receptor (sTfR), and C‐reactive protein were measured. Body iron stores were calculated from the sTfR/PF ratio. Socioeconomic factors, duration of exclusive breastfeeding, nature of complementary diet, and demographic characteristics were determined using a questionnaire. Mean ± SD age of the infants was 7.7 ± 0.8 months. Prevalence of anemia, ID, and IDA were 74.6%, 82.1%, and 64.9%, respectively. Months of exclusive breastfeeding correlated positively with Hb (r = 0.187; p < .05) and negatively with sTfR (r = −0.246; p < .05). sTfR concentrations were lower in infants exclusively breastfed at least 6 months compared with those exclusively breastfed for less than 6 months (7.6 (6.3, 9) vs. 8.9 (6.7, 13.4); p < .05). Controlling for gender, birth weight, and inflammation, months spent exclusively breastfeeding was a significant negative predictor of sTfR and a positive predictor of Hb (p < .05). The IDA prevalence in rural Kenyan infants is high, and greater duration of exclusive breastfeeding predicts better iron status and higher Hb in this age group.